Parallel Computation of Electric Potential in the EHD Ion-Drag Micropump and the Performance Analysis of the Parallel System - Shakeel Ahmed, Kamboh; Jane, Labadin; Andrew Ragai, Henry Rigit (2013)
The numerical solution of a computationally intensive model becomes more complex in terms of execution time required by a single processor. To speedup the computation, a suitable parallel computing architecture is required. This paper attempts to achieve a fast finite difference solution of electric potential in an EHD ion-drag micropump. A 2D Poisson’s equation is solved on a cluster of low cost computers using MATLAB. Numerical solution is obtained for the different mesh refinements and then the execution time, communication time, speedup and efficiency of parallel system are analyzed. The results showed that the speedup and efficiency of the system increases by increasing the grid points. The results also reveal that for each data size there is an optimum number of workers for obtaining the parallel numerical solution in minimum processing time.